Discourses of Mobility: Institutions, Everyday Lives and Embodiment. (14th March 2016) - Doughty, Karolina; Murray, Lesley
Abstract: This article seeks to contribute to the growing body of literature on the politics of mobility, revealing the ways in which the governing of mobility intersects with everyday mobile lives. We suggest that dominant and enduring institutional discourses of mobility, which are pervaded by a privileging of individualised automobility, can be conceptualised around a framework of morality, modernity and freedom. By examining everyday discourses of mobility in this context we highlight the ways in which these discourses reflect and resist normative sets of knowledge and practices. It is argued that by emphasising the everyday and mundane in an analysis of discourses of mobility, and acknowledging their situatedness in prevailing normative discourses, we are then able to focus on how movement is a social and cultural practice in constant negotiation and (re)production.